Digital economy enables common prosperity: Analysis of mediating and moderating effects based on green finance and environmental pollution - Zhang, Jie; Qian, Fangbin (Frontiers in Energy Research, 2023)
This study aims to explore the impact of the digital economy on common prosperity. For this reason, a bidirectional fixed effect model based on panel data of 30 provinces (cities and autonomous regions) in China is empirically tested. The results show that the digital economy can significantly improve the level of common prosperity, and has a positive impact on green and sustainable economic activities such as promoting environmental improvement, coping with climate change and resource conservation and efficient utilization, which is still valid after a series of robustness tests. It also demonstrates the role of green finance as a partial intermediary in the process of shared prosperity and as a negative regulator of environmental pollution. Analysis of regional heterogeneity shows that the enabling effect of the digital economy on common prosperity is more significant in eastern and central provinces, but not significant in western provinces. The results of this study have some reference significance for some countries, where the gap between rich and poor has widened during the epidemic, to narrow the income gap and provide ideas for the parties that made commitments at the Glasgow Climate Summit (COP26) to curb warming and reduce CO2 emissions. That is, continuous improvement of digital infrastructure; emphasis on the intermediary role of green finance and the negative regulating role of local environmental pollution levels; following the relative comparative advantages of regions and formulating differentiated policies for the development of the digital economy, etc.